Estimation in Binary Choice Models with Measurement Errors - David Edgerton; Peter Jochumzen (Lund University, School of Economics and Management, Department of Economics, 2003)
In this paper we develop a simple maximum likelihood estimator for probit models where the regressors have measurement error. We first assume precise information about the reliability ratios (or, equivalently, the proxy correlations) of the regressors. We then show how reasonable bounds for the parameter estimates can be obtained when only imprecise information is available. The analysis is also extended to situations where the measurement error has non-zero mean and is correlated with the true values of the regressors. An extensive simulation study shows that the estimator works very well, even in quite small samples. Finally the method is applied to data explaining sick leave in Sweden.
Additional information: Gauss program available.
Keywords: C25; C29; 330; Measurement error; errors-in-variables; probit; binary choice; bounds